1994
DOI: 10.1073/pnas.91.24.11427
|View full text |Cite
|
Sign up to set email alerts
|

Polysialic acid engineering: synthesis of polysialylated neoglycosphingolipids by using the polysialyltransferase from neuroinvasive Escherichia coli K1.

Abstract: The CMPs-dsac acid:polya2,8sialosyl sdalyltransferase (poIyST) (16), and leukemia (17). Consequently, polysialylation is an area of glycobiology that is having an important impact on studies in molecular microbiology, neurobiology, oncology, and cell and developmental biology.Our studies have focused on the unresolved problem of how synthesis and surface expression of the polySia glycotope is regulated in E. coli K1 (1), human neuroblastoma (18), and trout ovaries during oogenesis (19). Our aim has been to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…The requirement in PSA biosynthesis for an initiator of some sort derives from the inability of NeuS to synthesize PSA when presented with exogenous CMP-Sia (133). In contrast, NeuS will elongate (albeit with weak processivity) oligosialic acid acceptors containing three or more sialic acid residues (131) and will efficiently elongate certain ganglioside (sialylated mammalian glycolipid) acceptors in vitro (27,85). However, the fact remains that exogenous acceptors must already contain sialic acid, which does not help explain how at least the first sialic acid residue is added to the (unknown) endogenous acceptors in E. coli K1 PSA biosynthesis.…”
Section: De Novo Synthesismentioning
confidence: 99%
“…The requirement in PSA biosynthesis for an initiator of some sort derives from the inability of NeuS to synthesize PSA when presented with exogenous CMP-Sia (133). In contrast, NeuS will elongate (albeit with weak processivity) oligosialic acid acceptors containing three or more sialic acid residues (131) and will efficiently elongate certain ganglioside (sialylated mammalian glycolipid) acceptors in vitro (27,85). However, the fact remains that exogenous acceptors must already contain sialic acid, which does not help explain how at least the first sialic acid residue is added to the (unknown) endogenous acceptors in E. coli K1 PSA biosynthesis.…”
Section: De Novo Synthesismentioning
confidence: 99%
“…We concluded that all bacterial polySTs possess structurally similar acceptor binding sites. However, exogenous sialyl oligomers are poorly elongated (23)(24)(25), with most acting as acceptor for a single sialyl addition unless tethered to the membrane by a lipid anchor (26). Therefore, broadly extrapolating results derived from the use of exogenous acceptors to natural PSA elongation may be suspect to misinterpretation because of the failure to duplicate the in vivo process.…”
Section: Exogenous Acceptor Activities Of Heterologously Expressedmentioning
confidence: 99%
“…The a-2,6-sialyltransferase from Photobacterium damsela has been shown to transfer sialic acid to terminal galactose residues that are fucosylated or sialylated at the 2 or 3 position, respectively [I I], and such an acceptor specificity has not been reported for mammalian sialyltransferases. The a-2,8-sialyltransferase from E. coli has been used in the synthesis of glycosphingolipids [12], while crude extracts of E. coli expressing the N. meningitidis a-2,3-sialyltransferase have been used to sialylate a lactose derivative [ 131. The difference in their specificities makes these bacterial transferases important tools for the chemienzymatic synthesis of oligosaccharides with biological activity.…”
mentioning
confidence: 99%